A review of Delphi technique in developing Human Capital disclosure index - Salawati, Sahari (www.abacademies.org, 2018)
This paper reviews the Delphi technique, a primary data collection method that could be applied in an accounting study focusing on developing voluntary disclosure index. The application of Delphi technique to develop human capital disclosure index have given a new stage for an accounting study since Delphi technique were mostly applied in the scientific, technological and medical research only. This paper attempt to shows how such technique would overcome the problem associated with other primary data collection method of solely doing interview, questionnaire and focus group. The characteristics of Delphi technique initiated with the selection of panel experts, with anonymity, controlled feedback and statistical group response. The Delphi exercise could be conducted in two or more rounds until the consensus has been met where the index would finally being develop. This paper could give recommendation on how such technique could be applied in accounting study, in the future especially in developing disclosure index. Therefore, this paper attempt to show an example on how such technique could be applied in developing human capital disclosure index. The Delphi panel could be chosen from various background of human capital such as human resource manager, labor union and governmental department involves in human capital. The data collected from the panel experts than could be finalized through the measurement of consensus and developed the human capital disclosure index.